The Inverse Hall-Petch Effect in Nd:YAG Laser Irradiated Nickel. (2015) - Ali, Dilawar; Butt, M.Z.
Abstract: Mechanically polished 4N pure nickel specimens were irradiated in air with Nd:YAG laser for laser shots ranging from 1000 to 5000 with an increment of 1000. The structural and mechanical characterization of the specimens was done using X-ray diffractometer (XRD) and Vickers hardness tester. The XRD patterns exhibit variation in the intensity of diffraction peaks pointing to significant structural changes on laser irradiation. Crystallite size, uniform deformation energy density, lattice deformation stress, and lattice strain were determined by Williamson-Hall analysis using uniform deformation energy density model. All the four structural parameters referred to were found to increase linearly with laser shots. On laser irradiation, surface hardness of nickel first increases up to 3000 laser shots, and later on it decreases up to 5000 laser shots. Crossover from classical Hall-Petch relation to inverse Hall-Petch relation occurs at about 69 nm in the observed crystallite size range of 81 to 44 nm.